Implementasi Metode Analitycal Hierarchy Process (AHP) Pada Sistem Pendukung Keputusan Penilaian Kinerja Guru SD Negeri Taruna Karya IV Bandung - Senna Hendrian; Ade Kurnia Solihin; Galuh Krisna Dewanti (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
Taruna Karya IV State Elementary School (SD) Bandung City is one of the educational institutions in Bandung City, Taruna Karya IV Bandung State Elementary School organizes a teacher performance assessment program. In the process of assessing the performance of teachers at Taruna Karya IV Elementary School, Bandung City, the conventional method was used by filling out a questionnaire carried out by the school principal and the assessment team, then the questionnaire was recapitulated. The manual system and the number of teachers selected have caused school principals and the assessment team to experience difficulties in determining the teacher's decision with the best assessment. To find patterns in teacher performance assessment, a decision support system was built, through research. This research uses the Analytical Hierarchy Process (AHP) method. This method is used to evaluate and make multi-criteria decisions. It evaluates various alternatives based on different criteria and assigns a relative score to each alternative. Based on the results of this research, it produces better and more accurate calculations. If previously selection took 1 day, now with the decision support system the selection time is shorter. .